Vasoactive therapy in systemic sclerosis: real-life therapeutic practice in more than 3000 patients - Moinzadeh, Pia; Riemekasten, Gabriela; Siegert, Elise; Fierlbeck, Gerhard; Henes, Jörg Christoph; Blank, Norbert; Melchers, Inga; Müller-Ladner, Ulf; Frerix, Marc; Kreuter, Alexander; Tigges, Christian; Lahner, Nina Simone; et al. (The journal of rheumatology, 2016)
Objective. Vasculopathy is a key factor in the pathophysiology of systemic sclerosis (SSc) and the main cause for Raynaud phenomenon (RP), digital ulcers (DU), and/or pulmonary arterial hypertension (PAH). It is so far unknown how patients with SSc are treated with vasoactive agents in daily practice. To determine to which extent patients with SSc were treated with different vasoactive agents, we used data from the German Network for Systemic Scleroderma registry. - Methods. The data of 3248 patients with SSc were analyzed. - Results. Patients were treated with vasoactive drugs in 61.1% of cases (1984/3248). Of these, 47.6% received calcium channel inhibitors, followed by 34.2% treated with angiotensin-converting enzyme (ACE) inhibitors, 21.1% treated with intravenous (IV) prostanoids, 10.1% with pentoxifylline, 8.8% with angiotensin 1 receptor antagonists (AT1RA), 8.7% with endothelin 1 receptor antagonists (ET1RA), 4.1% with phosphodiesterase type 5 (PDE5) inhibitors, and 5.3% with others. Patients with RP received vasoactive therapy in 63.3% of cases, with DU in 70.1%, and with PAH in 78.2% of cases. Logistic regression analysis revealed that patients with PAH were significantly more often treated with PDE5 inhibitors and ET1RA, and those with DU with ET1RA and IV prostanoids. In addition, 41.8% of patients were treated with ACE inhibitors and/or AT1RA. Patients registered after 2009 received significantly more often ET1RA, AT1RA, and IV prostanoids compared with patients registered prior to 2005. - Conclusion. These data clearly indicate that many patients with SSc do not yet receive sufficient vasoactive therapy. Further, in recent years, a marked change of treatment regimens can be observed.